Secure Outsourced Aggregation via One-way Chains - Nath, Suman; Yu, Haifeng; Chan, Haowen (ACM SIGMOD, 2009)
We consider the Outsourced Aggregation model, where sensing services outsource their sensor data collection and aggregation tasks to third-party service providers called aggregators. As aggregators can be untrusted or compromised, it is essential for a sensing service to be able to verify the correctness of aggregation results. This work presents SECOA, a framework with a family of novel and optimally-secure protocols for secure outsourced aggregation. Our framework is based on a unified use of one-way chains. It supports a large and diverse set of aggregate functions, can have multiple hierarchically organized aggregators, can deterministically detect any malicious aggregation behavior without communication with sensors, and incurs a small and workload-independent communication load on sensors. We also present extensive evaluation results to demonstrate the feasibility of our framework.